The study of students' perceptions on the incorporation of computer-aided learning (CAL) material for medicinal chemistry teaching in the endocrine system & pharmacotherapeutics subject / Faridah Mohd Yunos - Mohd Yunos, Faridah (2013)
This thesis is written to in order to explore students' perceptions on the incorporation of Computer-Aided Learning (CAL) material into the current Medicinal Chemistry. CAL is identified not to replace but to complement the lecture-based learning that we are currently practiced in teaching Medicinal Chemistry. It is a type of teaching method which is flexible, self-accessed and self-instruction to provide students with the knowledge of Medicinal Chemistry in animations and audio. After analyzing the feedback questionnaires, it can be concluded that the material can be incorporated in Medicinal Chemistry teaching, but only after few improvements on the material is done. The improvements may include, the incorporation of more animations, graphics and audio into the program, the incorporation of instructions on how to use the programs, besides improving the buttons so that students will not have problem when using the program. The incorporation of quizzes and tests in the program should be implemented to assess students' understanding, besides adding in more information, and avoiding technical errors by increasing the number of personnel involved in preparing the material.